IDENTIFIKASI RISIKO KETERLAMBATAN PEMBANGUNAN JALAN TOL DENGAN PENDEKATAN RII (RELATIVE IMPORTANCE INDEX) (Studi Kasus Pembangunan Jalan Tol Binjai – Pangkalan Brandan) - Yanuar Widiandi Nufah; Ari Sandyavitri; Muhammad Yusa (Racic : Rab Construction Research, 2024)
The Binjai – Pangkalan Brandan Toll Road is part of the Trans Sumatra Toll Road based on Presidential Regulation Number 117 of 2015. Based on information from providers and users, it has experienced delays in completion. The aim of this case study is to identify factors causing delays, analyze risks using a probabilistic. It is hoped that the case study in this research combines 2 analytical methods to provide new input for researchers. The RII (Relative Importance Index) method found 5 dominant factors that most influenced the delay in this project, namely land permits, inadequate land investigations before design work, inaccurate data surveys (pre-design), design changes, permits related to the government.